Self-Regulated Writing Strategy as a Moderator of Metacognitive Control in Improving Prospective Teachers' Writing Skills - Haerazi Haerazi; Mohammad Kazemian (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This study was aimed at investigating the accuracy of self-regulated learning as a moderator of the metacognitive control to improve prospective teachers’ writing skills. This study was a mixed-method with the concurrent embedded strategy. The experimental study was carried out to meet the effectiveness of self-regulated learning to improve prospective teachers’ writing skills viewed from metacognitive skills. The research instruments used the observation sheet and writing test. The research findings showed that the self-regulated learning model was effective as a moderator of the metacognitive control in improving prospective teachers’ writing skills. It was proven by the result of the analysis factor of variance (ANOVA) that indicated that the significant value was lower than the sig. level 0.05. This study can be concluded that the self-regulated learning model was effective to improve prospective teachers’ writing skills viewed from metacognitive awareness.